ANALISIS PENGARUH WORK-LIFE BALANCE DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PT.TELKOMSEL, TBK BRANCH MALANG - Asepta, Uki Yonda; Maruno, Sekar Harumi Putri (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Employee is an asset to the company. Employees have a very important role for companies to achieve corporate goals. To keep employee performance to remain productive then it is necessary. Job satisfaction of an employee within the organization can’t be separated from career development, and work life balance. This research was conducted to determine the effect of Work-life Balance and Career Development on Job Satisfaction. This type of research uses a causal quantitative method. The data used for the research is primary data obtained from questionnaires distributed to 30 respondents employees of PT. Telkomsel, Tbk Branch Malang. The sampling technique used was the census. Data analysis method used is multiple linear regression. The results of research indicate that Work-Life Balance and Career Development affect simultaneously to Employee Satisfaction. Partially, work life balance significantly to employee job satisfaction. Career development has a significant effect on employee job satisfaction, will be falling again. The most dominant effect on employee job satisfaction is the work balance.